2021
DOI: 10.3390/oxygen1020009
|View full text |Cite
|
Sign up to set email alerts
|

The Reactive Oxygen Species Singlet Oxygen, Hydroxy Radicals, and the Superoxide Radical Anion—Examples of Their Roles in Biology and Medicine

Abstract: Reactive oxygen species comprise oxygen-based free radicals and non-radical species such as peroxynitrite and electronically excited (singlet) oxygen. These reactive species often have short lifetimes, and much of our understanding of their formation and reactivity in biological and especially medical environments has come from complimentary fast reaction methods involving pulsed lasers and high-energy radiation techniques. These and related methods, such as EPR, are discussed with particular reference to sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…Finally, D 2 O was used to determine the role of singlet oxygen ( 1 O 2 ) in degradation. Since the lifetime of 1 O 2 is 55 μs in D 2 O and 3.3 μs in H 2 O, 44 singlet oxygen-mediated reactions should be accelerated in D 2 O compared to H 2 O, due to the longer lifetime of 1 O 2 and hence the higher number of active species. In our case, the degradation was only slightly faster compared to H 2 O, indicating that 1 O 2 does not contribute significantly to the overall degradation mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, D 2 O was used to determine the role of singlet oxygen ( 1 O 2 ) in degradation. Since the lifetime of 1 O 2 is 55 μs in D 2 O and 3.3 μs in H 2 O, 44 singlet oxygen-mediated reactions should be accelerated in D 2 O compared to H 2 O, due to the longer lifetime of 1 O 2 and hence the higher number of active species. In our case, the degradation was only slightly faster compared to H 2 O, indicating that 1 O 2 does not contribute significantly to the overall degradation mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Enhanced therapeutic effect and eight-fold increase of accumulation compared to passive targeting were hence achieved in tumoral tissues of CT26 mice. [32] In the case of PSs that produce 1 O 2 and ROS with very short lifetimes, [33] it is particularly important for their efficacy to favor their cellular uptake through active targeting. Studies on active targeting revealed that the simple conjugation of moieties such as antibodies, [34] antibody fragments, [35] proteins, [36] and peptides [37] with molecular PSs can enrich their properties.…”
Section: Ii11 Nanoparticles To Improve Tumor Targeting and Cellular U...mentioning
confidence: 99%
“…[3,4] Among the others, 1 O 2 is a highly reactive, short-lived species and causes oxidation of organic matters. [5,6] PDT involving 1 O 2 species is considered to be localized as it has limited diffusion length. [7,8] To enhance the 1 O 2 generation, heavy non-metals (e. g., sulphur, bromine, iodine) or metals (Pt, Ir, etc.)…”
Section: Introductionmentioning
confidence: 99%